1973
DOI: 10.1111/j.1365-2222.1973.tb01312.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic changes in exercise‐induced asthma

Abstract: Summary Five patients with a history of post‐exercise bronchoconstriction and eleven control subjects were exposed to gradually increasing work loads on a bicyle ergometer. The asthmatic patients showed higher blood lactic acid levels at all work loads than the control subjects. In contrast to findings in the controls, the plasma free fatty acid in the asthmatics failed to ‘rebound’ following the cessation of exercise; and in two out of three patients plasma FFA did not rise after epinephrine injection. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1975
1975
1989
1989

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The neurological symptoms were believed to be the result of systemic alkalemia. During (2) and other laboratories (1,(3)(4)(5)(6)(7)(8)(9)(10)(11) has shown that postexertional bronchocon- (24) and perfusion of isolated skeletal muscle with hyperkalemic blood when the nerve is intact (25) produce an increase in ventilation typical of exercise, recent evidence demonstrates that neither hypocapnia nor hyperpnea are the mechanisms underlying exercise-induced asthma (26).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The neurological symptoms were believed to be the result of systemic alkalemia. During (2) and other laboratories (1,(3)(4)(5)(6)(7)(8)(9)(10)(11) has shown that postexertional bronchocon- (24) and perfusion of isolated skeletal muscle with hyperkalemic blood when the nerve is intact (25) produce an increase in ventilation typical of exercise, recent evidence demonstrates that neither hypocapnia nor hyperpnea are the mechanisms underlying exercise-induced asthma (26).…”
Section: Resultsmentioning
confidence: 99%
“…For a number ofreasons, this is an attractive hypothesis. First, the association between the induction of asthma and elevations in arterial hydrogen ion and/or lactate concentrations is quite common when one searches for it in the literature (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Second, because the acid end products of exercise are delivered to the airways and lung parenchyma by the bronchial and pulmonary arterial beds, and are freely permeable, they could possibly evoke intracellular events that promote generation or release of the mediators of immediate hypersensitivity (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…subjects repeated the protocol before and after inhalation of salbutamol aerosol, 1600 Htg daily for 18 days. This did not reduce the cAMP response to exercise, and we conclude that the diminished cAMP response of the asthmatic subjects was not caused by their medication.…”
mentioning
confidence: 99%